Determinants and promotion of self-regulated learning in educational contexts: the potential of web-based and attendance-based courses - Beek, Sophie van der (2021)
Self-regulated learning is an important skill to successfully study at school and university, but it is also of high importance for life-long learning (Commission of the European Community, 2000; Dignath & Büttner, 2008). The aim of this dissertation is to expand the knowledge about the trainability of self-regulated learning. To this end, the effectiveness of a web-based and an attendance-based self-regulated learning-training was compared, the role of individual characteristics as predictors of the effectiveness of self-regulated learning-training was examined, and the possibility of promoting the participation rate in voluntary self-regulated learning-training with minimal interventions was explored. Study I showed that students of an attendance-based and web-based course with the aim of fostering self-regulated learning were very satisfied with both course formats, self-regulated learning was considered useful for studying, and the subjective and objective increases in learning were high. Furthermore, the findings of Study I suggest that self-regulated learning can be fostered in the web-based course as effectively as in the attendance-based course as there were no group differences. Moreover, the findings suggest that it is of relevance to differentiate between two training phases that promote different processes: A theory phase that fosters declarative metacognitive knowledge on self-regulated learning and an implementation phase where strategies of self-regulated learning are practiced. The question of whether the effectiveness of a self-regulated learning-training intervention differs between participants depending on their individual characteristics was investigated in Study II. Results revealed that individual differences in personality – but not motivational factors – were related to the gain of self-regulated learning through respective training in a university context. More precisely, conscientiousness, agreeableness, and openness to experience significantly predicted increases in self-regulated learning, however, with varying importance for the two different phases of the training (theory versus implementation) and the training format (attendance-based versus web-based). Conscientiousness was related to both theory and implementation phases as well as both formats (attendance-based and web-based), agreeableness was only related to the theory phase and to the attendance-based format, and openness was as well only related to the attendance-based format but only in the implementation phase. Finally, while Study I and II were conducted at university, Study III focused on high-school students and addressed the question of whether the participation rate in voluntary web-based self-regulated learning-training can be promoted by minimal interventions on utility value and implementation intention. Unexpectedly, the minimal interventions had no effect on the participation rate, suggesting that these interventions are not effective per se, but rather context dependent. Apart from that, students’ expectation of success and average grade score proved to be positive predictors of training participation, which was also shown by latent profile-analyses. This suggests that initial motivation has an impact on voluntary training participation. In conclusion, the findings of the studies indicate that self-regulated learning can be fostered in web-based and attendance-based formats, that training success of self-regulated learning is related to personality factors, and that motivation plays a role concerning training participation. This dissertation significantly contributes to previous research by showing that both a theory phase and an implementation phase are crucial when employing a training program, and that the extent of training success seems to be affected by personality traits. Moreover, the findings give reason to evaluate critically in which contexts minimal interventions are successful. This dissertation has a number of implications for theory and for future research and it can also provide practical advice for educational contexts.
Keywords: Hochschulschrift